The Relationship Of Motor Skills And Health Related Fitness In Elementary School Students: Literature Review - Ahadi Priyohutomo; M.E Winarno; Imam Hariadi (Universitas Suryakancana, 2022)
The purpose of this study was to determine the relationship between motor skills and body composition, cardiorespiration, muscle strength and muscle endurance. This literature review method was carried out by researchers to collect articles based on inclusion criteria using the Google Scholar, PubMed and ScienceDirect databases. The process of searching for articles was carried out based on inclusion criteria consisting of research articles, published articles for 4 years, articles that have been indexed by Scopus (Q1-Q4), and a sample consisting of elementary school students. Articles that have been obtained from 3 databases, will then be selected at the article identification stage, the researcher finds 260 articles from Google Scholar, 43 articles from PubMed and 255 articles from ScienceDirect, at the duplication stage, 4 similar articles are found out of 554 articles that have been collected. In the filtering stage, the researcher analyzed by placing limits on titles and keywords so that they issued 526 articles and found 28 articles. The feasibility process was carried out to select 28 articles with limitations on journal qualifications, research variables and methods used, resulting in 19 articles and 9 articles being tested at the quantitative synthesis stage. At the inclusion stage, the researcher conducted a selection at the final stage by finding 9 articles that matched the inclusion criteria. The results of the analysis of the articles that have been carried out, there are 8 articles in total that have a relationship between motor skills and body composition, cardiorespiration, muscle strength and muscle endurance, while 1 article has no relationship between motor skills and body composition. The conclusion of the study showed that there was a relationship between motor skills and body composition, motor skills and cardiorespiratory, motor skills and muscle strength, and motor skills and muscle endurance. Key words: Motor Skills and Health Related Fitness